W.E.B. Du Bois and the souls of black folk - Shaw, Stephanie J. (Stephanie Jo), 1955- (Chapel Hill : The University of North Carolina Press, 2013)
In this book, the author brings a new understanding to one of the great documents of American and Black history. While most scholarly discussions of The Souls of Black Folk focus on the veils, the color line, double consciousness, or Booker T. Washington, the author reads Du Bois' book as a profoundly nuanced interpretation of the souls of Black Americans at the turn of the twentieth century. Demonstrating the importance of the work as a sociohistorical study of Black life in America through the turn of the twentieth century and offering new ways of thinking about many of the topics introduced in Souls, the author charts Du Bois' successful appropriation of Hegelian idealism in order to add America, the nineteenth century, and Black people to the historical narrative in Hegel's philosophy of history. The author adopts Du Bois' point of view to delve into the social, cultural, political, and intellectual milieus that helped to create The Souls of Black Folk.
Introduction -- Striving : work, culture, and liberty -- The sovereignty of Soul -- "The talented tenth" revisited -- Spirit : Alexander Crummell, prophets, and destiny -- Reading Souls with Phenomenology : a preface to chapter 5 -- The religion and songs of Souls. The art and religion of Souls and Hegel's "Experience of consciousness" ; The songs of Souls and Hegel's "Philosophy of spirit" ; The songs of Souls and Hegel's "Absolute Knowledge" -- Conclusion : "O world of worlds, how shall man make you one?"
Includes bibliographical references and index.
Online resource (HeinOnline, viewed August 4, 2021).
English.
eBooks on EBSCOhost
Keywords: Du Bois, W. E. B. -- 1868-1963.; Du Bois, W. E. B. -- 1868-1963 -- Criticism and interpretation; Du Bois, W. E. B. -- 1868-1963 -- Criticism and interpretation; Du Bois, W. E. B. -- 1868-1963.; Du Bois, W. E. B. -- 1868-1963; Souls of Black folk (Du Bois, W. E. B.); POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; HISTORY -- United States -- 20th Century; Criticism, interpretation, etc